Influence of secondary forest canopy towards interception rate in hydrological cycle of Tasik Chini, Pahang, Malaysia - Nor Rohaizah Jamil,; Mohd. Ekhwan Toriman,; Mushrifah Idris,; Lim, Wei Jing (Universiti Kebangsaan Malaysia, 2010)
Part of a rainfall is captured by the crowns of the trees and other surfaces as interception, which is then evaporated back into the atmosphere. Water moves down through the forest canopy via two mechanisms; stemflow and throughfall processes. Stemflow refers to the total quantity of rain water which reach the ground through tree stems and branches. Throughfall in the other hand, is the tendency of the rainfalls to penetrate the forest canopy directly through the spaces between the leaves or by dripping from the leaves, twigs, and branches. Both components were measured in an interception plot size 100 ¥100 m2 in a secondary tropical forest at Tasik Chini. Thirty tree samples were used and each tree was well-identified based on their species, family, diameter breast height (DBH), canopy size and its density. In this study, the data were collected based on two rainfall events, namely in November 2007(44.51% in throughfall form and 55.49% in stem flow form) and rainfall distribution on December 2007 (39.65% in throughfall form and 60.35% in stem flow form). This interception study provided essential information on how the function of the forest can affect the crucial hydrological cycle occurring within this forest ecosystem and the wetland water balance.